Beyond clinical risk: tackling loneliness through a population health lens - Zeas-Sigüenza, Ananda; Ruisoto, Pablo; Koldewyn, Kami; Muntané, Ferran; Benach, Joan (Frontiers in Psychology, 2025)
Loneliness is a distressing emotional state that arises from unmet social needs, particularly the quality—rather than merely the quantity—of social connections. While it serves an adaptive function by signaling social disconnection and motivating reconnection, chronic loneliness is a well-established risk factor for adverse mental and physical health outcomes. Recognizing its growing prevalence and health burden, the World Health Organization (WHO) has identified loneliness as a public health priority. To date, most research and interventions have focused on high-risk individuals, mainly within clinical populations, often addressing loneliness only after it becomes severe and entrenched. This paper argues for a paradigm shift toward population-level interventions that targets the broader social and environmental determinants of loneliness. Specifically, we propose a loneliness spectrum model and a systemic intervention framework that targets structural determinants, positioning loneliness prevention as a fundamental public health strategy through nature-based and community-driven interventions.